Innovation, Institution und Region: Zur Diskussion über nationale und regionale Innovationssysteme - Bathelt, Harald (ERDKUNDE, 2003)
This paper begins with the proposition that territorial production configurations continue to remain important despite the fact that globalization processes are antagonistic. From this, we pose the question as to whether such production and innovation contexts can be conceptualized as territorial systems. Based on a discussion of the characteristics of social systems, such systems are defined as being capable of self-reproduction through ongoing communication. Further, they are autonomous with respect to the reproduction of their very basic structure. Social systems thus perpetuate and deepen the difference which exists between themselves and their environment. We argue that it makes sense to use this concept to analyze national innovation systems which are characterized by positive feedback loops and reflexive practices between production, institutions and innovation. This leads to ongoing specialization processes within an economy which are different from those of other economies. Processes of ‚othering' are driven by day-to-day interaction and communication within the system, or, in other words, by the continued reproduction of special semantics and institutional arrangements. In contrast, the conceptualization of regional (subnational) innovation systems appears problematic. At the regional level, it is unlikely that a self-referential system can develop because production and innovation normally depend on national institutions and other external influences to a great extent. Regional production configurations thus do not have the potential to gain and retain structural independence and reproduce themselves.